FORMATION OF FARMING ENTERPRISES AND THEIR OUTCOMES IN THE LIVESTOCK SECTOR IN SURXONDARYO REGION - Jumaeva Shohida Chorievna (Scholar Express Journal, 2025)
This article examines the establishment of farming enterprises in the livestock sector in Surxondaryo Region and analyzes their outcomes. The study explores the organizational models of these farms, the effectiveness of their management, and the impact on local economic development. Examples and statistical data are used to illustrate the results achieved by these enterprises and their contribution to improving livestock production and rural livelihoods.
Keywords: Surxondaryo Region; livestock sector; farming enterprises